Risk Assessment and Management of Exposure of Health Care Workers In The Context of COVID-19 According to WHO in Egypt (Indian Journal of Public Health Research & Development, 2020)
Background: Infection prevention and control strategies of WHO to prevent transmission ofCOVID-19 in health-care settings comprise the following: early finding, source, organizational, andenvironmental controls, and Personal Protective Equipment (PPE). WHO reported on 22 April 2020 thatestablished three congresses: Personal Protection Equipment (PPE), Diagnostics and Clinical care to reportglobal market shortage for critical supplies required for the global COVID-19. The aim of the current studyto evaluate risk assessment and management of exposure of health care workers in the context of COVID-19.Research Design: A prospective, descriptive research design was utilized in this study. A random sample of230 responds of HCWs, via an internet survey. Tool: one tool was used; risk assessment and managementof exposure of health care workers in the context of COVID-19. Results: The study reported the highrisk of COVID-19 to three clusters: 1st group who didn’t wear PPE with infected cases (20%), 2nd groupof HCWs who used a PPE but not with all cases or contact with the environment of patients, (20 to 35 %)and 3rd group (34%), of high risk who exposed to accident biological material during interaction with aCOVID-19 patient. WHO surveillance raises the staff’s attention to PPE management and recommendation.Recommendations: Health care sitting should Provide her staff with enough PPE, and demonstrate thepurpose and use of each PPE. Update the policy of PPE according to WHO recommendations.
Keywords: Risk Assessment, Health Care Workers, COVID-19, PPE